Endogenous calcitonin regulates lipid and glucose metabolism in diet-induced obesity mice. Issue 1 (December 2018) - Nakamura, Misa; Nomura, Sachiko; Yamakawa, Tadashi; Kono, Ryohei; Maeno, Akihiro; Ozaki, Takashi; Ito, Akitoshi; Uzawa, Toyonobu; Utsunomiya, Hirotoshi; Kakudo, Kennichi
Abstract Calcitonin (CT) plays an important role in calcium homeostasis, and its precursor, proCT, is positively associated with the body mass index in the general human population. However, the physiological role of endogenous CT in the regulation of metabolism remains unclear. Knockout mice with gene-targeted deletion of exon 4 ofCalca (CT KO) were generated by targeted modification in embryonic stem cells. Male mice were used in all experiments and were fed a slightly higher fat diet than the standard diet. The CT KO mice did not exhibit any abnormal findings in appearance, but exhibited weight loss from 15 months old, i.e., significantly decreased liver, adipose tissue, and kidney weights, compared with wild-type control mice. Furthermore, CT KO mice exhibited significantly decreased fat contents in the liver, lipid droplets in adipose tissues, serum glucose, and lipid levels, and significantly increased insulin sensitivity and serum adiponectin levels. CT significantly promoted 3T3-L1 adipocyte differentiation and suppressed adiponectin release. These results suggested that CT gene deletion prevents obesity, hyperglycemia, and hyperlipidemia in aged male mice. This is the first definitive evidence that CT may contribute to glucose and lipid metabolism in aged male mice, possibly via decreased adiponectin secretion from adipocytes.